Genome-wide identification of the VOZ transcription factors in tomato (Solanum lycopersicum): their functions during fruit ripening and their responses to salinity stress - Uluışık, S.; Kıyak, A.; Kurt, Fırat; Filiz, E. (Taylor and Francis Ltd., 2022)
As a plant-specific transcription factor, vascular plant One-Zinc-finger (VOZ) is involved in the regulation of many biological processes. VOZ genes in tomato have not been analysed comprehensively so far. In this study, two SIVOZs were identified on a genome-wide scale in tomato and analysed using various bioinformatics methods. According to Ka/Ks ratio, SlVOZ proteins are being changed by evolutionary processes to adapt to changing growth and stress conditions. Protein structure and phylogenetic analyses also indicated that transcriptional regulations of SlVOZs were controlled in a specific manner related to developmental stages and abiotic stress conditions. Digital expression results, in particular, showed that SlVOZs are not only active during different growth status of tomato but are also involved in abiotic stress response mechanism. Nonetheless, SlVOZ1 is expressed higher in both developmental stages and under salt stress conditions, confirmed by RT-qPCR. The co-expression maps constructed using RNA-seq data showed that SlVOZ2 was associated with the genes involved in hormonal regulation, formation of fruit shape, secondary wall biosynthesis and in plant development. Overall, it can be concluded that SlVOZs are not only important for plant growth and development but may also be part of the salt stress response mechanism. © 2022 Journal of Horticultural Science & Biotechnology.
Keywords: Bioinformatics; co-expression; fruit ripening; salt stress; tomato